LIGHT AND FOOD INDUSTRY DURING THE WAR YEARS: ACHIEVEMENTS AND PROBLEMS (1941-1945) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
War in the years industry of enterprises To Uzbekistan relocation as a result, the production capacity of light industry was also focused on the implementation of military tasks and from the news big in scope work go ahead owner was of modern light industrial enterprises, Central In Asia , including Uzbekistan building to be done necessary turned and carved .